Produção microbiológica de ácido propiônico, 1,3-propanodiol e hidrogênio a partir de glicerol bruto em reator anaeróbio de leito fluidizado - Nazareth, Talita Corrêa (Universidade Federal de São Carlos, 2015)
This study aimed to produce propionic acid, 1,3-propanediol and hydrogen in anaerobic fluidized bed reactor with grounded tire as support material for immobilization of biomass. The experiment took place during 278 days in six distinct phases distributed according to the hydraulic retention time (HRT), which ranged between 8 and 0.5 h. The reactor was maintained at mesophilic conditions (30 ° C) with controlled pH between 4.5 and 5.5 and crude glycerol as carbon source at a concentration of 5 g L-1. The inoculum used in the experiment was derived from the processing of poultry slaughterhouse wastewater station. The results show that the consumption of substrate conversion reached the highest value (89.8 %) in HRT of 6 hours. The biogas produced was composed of H2 and CO2 and the greatest recorded content of H2 has been reached (81.2%) in HRT of 4 hours. The principal soluble metabolite produced were propionic acid and 1,3-propanediol, with maximum yields of 1,77 and 0,82 mol.molglicerol -1, respectively. Both maximum yields were achieved in HRT of 8 h. At all stages of this work occurred predominantly propionic acid, with maximum molar percentage (96,9 %) achieved in HRT of 0,5 h. The second predominant metabolite obtained was 1,3- propanediol, achieving greater molar percentage (29.4%) in HRT of 6 hours.
Keywords: Ácido propiônico; 1,3-propanodiol; Hidrogênio; Reator anaeróbio de leito fluidizado; Glicerol bruto; H2; Anaerobic fluidized bed reactor; Crude glycerol; Tires; TDH; Propionic acid; ENGENHARIAS::ENGENHARIA QUIMICA